Resurrection after death between religious myths and the Old Testament - nuri, janan; Hamad , Khayal (Islamic Sciences Journal, 2023)
Religious myths are an essential part of the formation of human thought and civilization,Thus, a group of ancient religions and beliefs arose, which were rituals, legends, magic and sorcery, and an attempt to control hidden forces and draw closer to them using certain rites, such as offering sacrifices and offerings. Then, human religions such as, religion appeared in Mesopotamia civilization, Hammurabi canons, Greek and Zoroastrian divine philosophies in Persia, Confucianism, Buddhism and Taoism in the Far East, Hinduism in India, Ammonia and Akhenatene in the Pharaohs and others, until the revelation of monotheistic religions of Judaism, Christianity, and Islam . The books of the Torah contained a lot of important historical information of ancient civilizations. The Hebrews of that civilization took a lot in the field of myths, stories, and acquaintances and included them in their Torah through translation. The impact of the Jews on the etiquette of the Mesopotamian civilization was reflected in the development of their basic religious beliefs through what They quoted and translated from that civilization. This was clearly beyond doubt, through what came in the biblical texts that carried many books and religious poems among its Asfar of the Torah.